2019
DOI: 10.3390/cells8101176
|View full text |Cite
|
Sign up to set email alerts
|

The Incomplete Puzzle of the BCL2 Proteins

Abstract: The proteins of the BCL2 family are key players in multiple cellular processes, chief amongst them being the regulation of mitochondrial integrity and apoptotic cell death. These proteins establish an intricate interaction network that expands both the cytosol and the surface of organelles to dictate the cell fate. The complexity and unpredictability of the BCL2 interactome resides in the large number of family members and of interaction surfaces, as well as on their different behaviours in solution and in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 105 publications
(146 reference statements)
1
24
0
Order By: Relevance
“…In general, the Bcl-2 family can be subdivided into three groups: (a) antiapoptotic Bcl-2 proteins, including Bcl-2, Bcl-xL, and Mcl1, that counteract MOMP by binding to and thus inhibiting pro-apoptotic family members; (b) the pro-apoptotic effectors Bax and Bak, that upon activation integrate, oligomerize, and form pores in the mitochondrial outer membrane; (c) BH3-only proteins like Bim, Bid, Puma, and Noxa, which are direct activators of Bax/Bak and/or block antiapoptotic Bcl-2 family members. 111,112 Various signaling pathways regulate the relative abundance as well as activity of BH3-only proteins, making them important upstream sensors that fine-tune the antagonizing forces between antiapoptotic and pro-apoptotic Bcl-2 proteins during apoptotic signaling. Pro-and antisurvival signals are thus integrated by the highly complex interactome and balance of Bcl-2 family members, deciding over the cellular fate by controlling integrity of mitochondria.…”
Section: Lrh-1 As a Regulator Of Cell Survival And Mitochondrial Apmentioning
confidence: 99%
“…In general, the Bcl-2 family can be subdivided into three groups: (a) antiapoptotic Bcl-2 proteins, including Bcl-2, Bcl-xL, and Mcl1, that counteract MOMP by binding to and thus inhibiting pro-apoptotic family members; (b) the pro-apoptotic effectors Bax and Bak, that upon activation integrate, oligomerize, and form pores in the mitochondrial outer membrane; (c) BH3-only proteins like Bim, Bid, Puma, and Noxa, which are direct activators of Bax/Bak and/or block antiapoptotic Bcl-2 family members. 111,112 Various signaling pathways regulate the relative abundance as well as activity of BH3-only proteins, making them important upstream sensors that fine-tune the antagonizing forces between antiapoptotic and pro-apoptotic Bcl-2 proteins during apoptotic signaling. Pro-and antisurvival signals are thus integrated by the highly complex interactome and balance of Bcl-2 family members, deciding over the cellular fate by controlling integrity of mitochondria.…”
Section: Lrh-1 As a Regulator Of Cell Survival And Mitochondrial Apmentioning
confidence: 99%
“…The BH3 motif is composed of 9 to 15 amino acids and is uniquely conserved across all BCL-2 family members [16]. BH3 interactions are responsible for orchestrating the BCL-2 interactome via a BH3-into-hydrophobic groove mechanism [17,18], which allows the formation of homo-and heterodimers that control apoptotic function [19]. Minor alterations in the amino acid sequences of the binding grooves and BH3 domains control the specificity of these interactions.…”
Section: The Bcl-2 Superfamily Controls the Intrinsic Apoptosis Pathwaymentioning
confidence: 99%
“…Membrane insertion and BAX oligomerization are the rate limiting steps for intrinsic apoptosis to proceed. Changes in the mechanical properties of the mitochondrial membrane may regulate BCL-2 proteins, or the membrane itself may have direct effects in modulating BCL-2 family member function [19]. One study has reported increased resistance for BAX-BCL-xL complexes when membrane inserted, and it is proposed that the inhibition of BAX oligomerization by BCL-2 proteins in the context of cellular membranes may be an effective means to allow the cell to avoid BAX activation [167].…”
Section: Future Directions and Challengesmentioning
confidence: 99%
“…The current Special Issue of Cells , “Regulation of Apoptosis by the Bcl-2 Family of Proteins”, gives a sense of the recent advances in all aspects of apoptotic regulation, ranging from in vitro biophysical characterization, through in vivo cellular studies, to preclinical and clinical studies of cancer treatments. The contributions to this Special Issue include three original articles, employing sophisticated techniques to gain important insights into the mechanisms of apoptotic regulation [ 1 , 2 , 3 ]; a thought-provoking perspective article [ 4 ] and two conceptual reviews, discussing state-of-the-art developments in drugs targeting anti-apoptotic Bcl-2 proteins [ 5 , 6 ]. Despite the collection of articles not encompassing all aspects of apoptosis, the following two general themes can be clearly identified.…”
mentioning
confidence: 99%
“…A major knowledge gap is, therefore, the lack of accurate molecular pictures of protein-lipid interactions, protein refolding on the membrane and protein–protein interactions in the context of membrane-refolded conformations. The perspective article by Flores-Romero and García-Sáez [ 4 ], entitled The Incomplete Puzzle of the BCL2 Proteins , provides a critical examination of the recent insights and remaining challenges in this excitingly complex field of Bcl-2 proteins. It concludes that “we still fail to understand the contribution of mitochondrial lipids in modulating their activation, oligomerization and formation of supramolecular structures at apoptotic foci during and after MOMP.” One step toward completing the outlined puzzle is presented by Vasquez-Montes and co-workers [ 3 ], who use a battery of spectroscopic tools including single-molecule Förster Resonance Energy Transfer to test the hypothesis of the lipid-dependent conformational switching in the apoptotic inhibitor Bcl-xL.…”
mentioning
confidence: 99%